Approaches in Enhancing Antioxidant Defense in Plants - Fujita, Masayuki; Hasanuzzaman, Mirza (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, "Approaches in Enhancing Antioxidant Defense in Plants" published 13 original research works and a couple of review articles that discuss the various aspects of plant oxidative stress biology and ROS metabolism, as well as the physiological mechanisms and approaches to enhancing antioxidant defense and mitigating oxidative stress. These papers will serve as a foundation for plant oxidative stress tolerance and, in the long term, provide further research directions in the development of crop plants' tolerance to abiotic stress in the era of climate change.